The Relationship Between Physical Quality Of The House, Smoking Behavior And Incidence Of Pulmonary Tuberculosis In The Working Area Of The Medan Helvetia Health Center - Siti Nur Aisyah; Meutia Nanda (Universitas Muhammadiyah Palu, 2026)
Pulmonary Tuberculosis in the Medan Helvetia Community Health Center (Puskesmas) area ranks fourth with 106 cases. This study aims to determine the relationship between physical housing quality, smoking behavior, and mosquito coil use with the incidence of pulmonary tuberculosis in the Medan Helvetia Community Health Center area. This quantitative study used a case-control design. The sample size was 106 respondents, consisting of 53 cases and 53 controls. This test was conducted using the Chi-Square statistical test with SPSS 20. The results of this study found a relationship between the variables of Physical Home Quality, which encompass five components: Room Temperature (p-value = 0.000; OR = 9.518), Home Ventilation (p-value = 0.000; OR = 6.644), Occupancy Density (p value = 0.000; OR = 4.689), Lighting (p-value = 0.000; OR = 4.138), and Humidity (p-value = 0.001; OR = 4.013). The variable, Smoking Behavior (p-value = 0.000; OR = 25.941), was associated with the incidence of Pulmonary Tuberculosis in the Medan Helvetia Community Health Center (Puskesmas Medan) work area. Meanwhile, the variable